Experimental investigation of leading-edge tubercle and surface corrugation effects on cavitation and noise in partially cavitating twisted hydrofoils - Celik, Fahri; Usta, Onur; Oksuz, Sinem; Delikan, Mehmet; Kara, Erdinc; Ozsayan, Selahattin; Unal, Ugur Oral (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study investigates the effects of leading-edge tubercles and surface corrugations on cavitation behavior and noise generation in twisted hydrofoils. Cavitating flow tests were conducted in a cavitation tunnel on three hydrofoil models with an aspect ratio (AR) of 3.33. The models include a Baseline version with the standard NACA 0015 section and two modified versions derived from the Baseline geometry by incorporating tubercles on the leading edge and corrugations on the surface. Cavitation development was recorded using a high-speed camera and analyzed in terms of cavitation periods, cycle stages, sheet cavitation areas, and maximum cavitation lengths. Sound pressure level (SPL) measurements were conducted using a hydrophone for the Tubercled and Corrugated models. Experimental uncertainty analysis was performed for the investigated parameters, including cavitation area, maximum cavitation length, cavitation period, and cavitation-induced noise. Additionally, experiments were performed on the Corrugated and Tubercled models to investigate the effects of Reynolds number and cavitation number on cavitation development and cavitation-induced noise. Cavitation tests under identical conditions revealed that the Corrugated model exhibited a slightly larger sheet cavitation area and a longer period compared to the Baseline model, while the Tubercled model's cavitation area and period were approximately 70% and 50% of those of the other models, respectively. In the uncertainty analysis, the total uncertainty for the cavitation area was determined to be 5.2%, while the total uncertainty associated with the noise measurement was calculated as 4.2%. Noise measurements confirmed that the Tubercled hydrofoil exhibited superior acoustic performance, generating lower sound pressure levels across most frequencies. Increasing Reynolds number and decreasing cavitation number led to higher noise levels in all configurations. It is anticipated that this study provides valuable insights into cavitation and noise characteristics of twisted hydrofoils with leading-edge tubercles and surface corrugations.
Keywords: Twisted hydrofoil; Cavitation; Tubercle; Corrugation; Experiment; NACA 0015; FLOW; Engineering; Oceanography